2005
DOI: 10.1158/1055-9965.epi-04-0424
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Cancer Susceptibility and THRA1 and BAT-40 Repeats Polymorphisms

Abstract: Although genetic and environmental factors have been identified in the etiology of thyroid cancer, the specific genetic implications in sporadic thyroid tumors are poorly understood but, as in other common cancers, low-penetrance susceptibility genes are believed to be crucial in the tumorigenesis processes. Here, we have carried out a casecontrol study to investigate whether there is an association between THRA1 CA repeat or BAT-40 A repeat polymorphisms and thyroid cancer risk. The THRA1 repeat resides in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…We previously reported that the chromosome 1p12-13 was associated with thyroid cancer susceptibility in a case-control study using the microsatellite BAT-40 marker (13). In the present study, we have conducted a fine mapping of the susceptibility loci in this region by extending the analysis to an average distance of 2.4 Mb.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…We previously reported that the chromosome 1p12-13 was associated with thyroid cancer susceptibility in a case-control study using the microsatellite BAT-40 marker (13). In the present study, we have conducted a fine mapping of the susceptibility loci in this region by extending the analysis to an average distance of 2.4 Mb.…”
Section: Resultsmentioning
confidence: 92%
“…Thus, association studies aimed to identify genes for thyroid cancer risk have been recently published (9-12), although no specific genes for thyroid cancer susceptibility have yet been described. Our previous study, using the BAT-40 marker in a casecontrol study, indicated that the chromosome 1p12-13 is related to thyroid cancer susceptibility (13). Therefore, in the present study, we aimed to map the susceptibility loci on this region.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A series of promising reports identifying polymorphisms in germline DNA have been published in an effort to delineate polygenic models of thyroid cancer susceptibility and prognosis (80)(81)(82). Such models are particularly interesting since they may help select individuals for specific chemopreventive interventions and determine which patients with nodules or with microcarcinomas are most likely to benefit from specific therapies.…”
Section: Detoxification Systems and Thyroid Carcinoma Susceptibilitymentioning
confidence: 99%
“…In these latter types of studies, a special interest should be given to SNPs within genes specifically involved in the thyroid function. In fact, although these studies are not frequently reported in the literature, SNPs within thyroglobulin ( TG ) and in thyroid‐related hormone receptors loci, such as THRA1 (thyroid hormone receptor type alpha‐1), are found associated with increased risks . Studies on genetic polymorphisms within other genes relevant for the thyroid functions, such as thyroperoxidase ( TPO ), are not reported.…”
mentioning
confidence: 99%